A comparative geological study of some major kimberlite pipes in the Northern Cape and Orange Free State - Clement, Cameron Roger (Department of Geological Sciences, 2015)
In the first part of this thesis the petrological status of 'kimberlite' is defined and mineralogical and textural classifications which allow systematic documentation and collation of these complex rocks are evaluated. Quantitative mineralogical classification based on the modal abundances of the matrix minerals is advocated. A textural classification is adopted within which different textures are related to different modes and conditions of kimberlite emplacement. In the subsequent and major part of the thesis the results of a comparative geological study of six diamondiferous kimberlite pipes are reported. The pipes concerned are the De Beers, Wesselton, Dutoitspan, Bultfontein, Finsch and Koffiefontein occurrences (collectively termed the KIMFIK pipes).